2014
DOI: 10.1111/ijd.12590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loratadine and cetirizine on serum levels of neuropeptides in patients with chronic urticaria

Abstract: H1-receptor inhibiting drugs, namely loratadine and cetirizine, were frequently used in treatment of chronic urticaria. Urticarial weal and flare reactions, a neurogenic reflex due to neuropeptides, were reported to be more effectively inhibited by cetirizine than loratadine. The aim of this study was to determine and compare the effects of systemic loratadine and cetirizine treatments on serum levels of selected neuropeptides in chronic urticaria. Treatment groups of either systemic loratadine or cetirizine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…3,4 A second-generation antihistamines turned loratadine is one of the most commonly used medicines for clinical treatment of chronic urticaria. 5,6 Desloratadine citrate disodium is the latest antihistamine agent. Pharmacological pharmacokinetic studies have shown that it has higher solubility than other second-generation antihistamines with better safety, so it may have better efficacy for the treatment of chronic urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A second-generation antihistamines turned loratadine is one of the most commonly used medicines for clinical treatment of chronic urticaria. 5,6 Desloratadine citrate disodium is the latest antihistamine agent. Pharmacological pharmacokinetic studies have shown that it has higher solubility than other second-generation antihistamines with better safety, so it may have better efficacy for the treatment of chronic urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Metz et al found that serum SP is upregulated in CSU, and levels were correlated with disease activity [58, 69 ]. Serum levels of neuropeptides such as neuropeptide Y, vasoactive intestinal peptide, stem cell factor and nerve growth factor were shown to be significantly decreased after treatment with H1 antihistamines in CSU patients [70, 71 ].…”
Section: Potential Therapeutic Targets For Novel Drug Approachesmentioning
confidence: 99%
“…An RCT showed that levocetirizine and desloratadine were able to reduce the plasma levels of pro-inflammatory cytokines, including IL-1β and IL-8, in patients with allergic rhinitis 15 . Other antihistamines, such as loratadine and cetirizine, have been reported to reduce serum neuropeptides, including neuropeptide Y, vasoactive intestinal peptide stem cell factor, and NGF 16 . A study of stimulated NGF secretion by histamine from cultured astrocytes showed that the H1-histamine receptor was involved in the signal transduction pathway of NGF 17 .…”
Section: Discussionmentioning
confidence: 99%